Analisis Perbandingan Kualitas Produk Amplikon Gen PMSA2 Antara Spesimen Spot Darah Kering dan Vena - Arsyam Mawardi; Hendra K. Maury; Yustinus Maladan (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
This study is aimed to analyze the comparative quality of PMSA2 gene amplicon product stability from two different specimen sources, spot specimens of dried blood and venous blood, as well as selecting the best storage method for specimens of blood samples. This research uses descriptive laboratory research methods. The research began with the process of sample preparation for dried blood spot and venous blood, each using Whatman 903 paper and vacuum tubes containing EDTA, isolating genomic DNA using KIT Zymo Research, amplification of PMSA-2 genes with PCR, detection of PCR products through electrophoresis, measurement of DNA concentration and absorbance, and data analysis. The results of this study are expected to be a source of information about the advantages of two specimen storage methods for clinical blood samples, as well as providing a clear description of the quality of each specimen storage method based on the quality of its amplicon products. The results showed that a total of ten medical samples of dried blood spot and ten venous blood were isolated from the genomic DNA of ten and nine, respectively. PMSA2 gene amplicons detected were seven in venous blood and six in dried blood spot. Venous blood specimens have sensitivity in detecting PMSA genes in samples with the highest value of 554 ng / μL and purity of 2,007 (WB7), and concentration of 550.2 and highest purity of 2,076 (WB10). Venous blood storage techniques using categorized vacuum tubes are effective in the detection of PMSA2 genes and have time efficiency in the process. From these results it was also concluded that the comparison analysis of amplicon products between venous blood specimens was better, more stable and efficient than dry blood spot specimens, thus recommending storage of venous blood specimens using vacuum tubes as the best storage method of blood sample specimens.